Nilai-Nilai Pendidikan Karakter Dan Moral Dalam Film Ali Dan Ratu-Ratu Queens - Ria Sri Wahyuni; Ratu Wardarita; Emmawati Emmawati (Jurnal Pembahsi (Pembelajaran Bahasa Dan Sastra Indonesia), 2023)
The problem of this research is what are the values of character education and morals in the film Ali and the Queens of Queens. The purpose of this study is to describe the values of character and moral education in the film Ali dan Ratu-ratu Queens which specializes in character education religious values, nationalism values, integrity values, independent values and mutual aid values as well as moral values in the form of human relations with God, human relations with oneself, human relations with humans and human relations with nature. The research method used in this method is the qualitative descriptive method. The source of this data and the object of study is sourced to the films Ali dan Ratu-ratu Queens. The data analysis technique used is a documentation technique. The results of the analysis obtained are in the form of character and moral education values. The values of character education consist of 5, namely (1) religious values (2) nationalist values (3) independent values (4) mutual aid values and (5) integrity values. Moral values are divided into 4 parts, namely (1) moral values contained in man's relationship with God, (2) moral values contained in the relationship between humans and fellow humans, (3) moral values contained in the relationship between humans and fellow humans, and (4) moral values contained in man's relationship with the universe.